Membangun Destinasi Wisata Ramah Anak dan Budaya Bahasa di Desa Daling - Alsabarni, Alsabarni; Siregar, Nurkoimah; Fitri, Maliyani; Marlina, Marlina (TSAQOFAH, 2025)
The increasing number of tourist visits to a destination indirectly contributes to regional income growth and opens up employment opportunities, thereby improving the welfare of the surrounding community. This study aims to identify the supporting facilities that have been designed by Daling Village and evaluate their alignment with the needs of child tourists without altering the existing main design. Additionally, the study analyzes factors influencing children’s satisfaction with the available facilities to provide recommendations for developing child-friendly tourism destinations in Central Aceh Regency. A qualitative approach with a descriptive method was employed, focusing on in-depth understanding of the actual processes and conditions in the field. The findings indicate that although tourism destinations offer various economic and social benefits, improvements are still needed in areas such as tourist infrastructure, culturally appropriate language use tailored to child tourists, and the reinforcement of sustainable development principles. This study recommends the development of strategies to address barriers in building child-friendly tourism destinations while preserving local character to support an inclusive and educational tourism experience.